Connectivity of superpower graphs of some non-abelian finite groups - Kumar A.; Selvaganesh L.; Tamizh Chelvam T. (My University, 2025)
For a finite group G, the superpower graph S(G) of G is an undirected simple graph with vertex set G and two vertices in G are adjacent in S(G) if and only if the order of one divides the order of the other in the group G. In this paper, we give sharp bounds for the vertex connectivity of superpower graphs S(D2n) and S(T4n) of dihedral group D2n and dicyclic group T4n. © 2023 World Scientific Publishing Company.